Flood simulation using HEC-HMS 4.8 for ungauged catchment during extreme events in Lui River, Hulu Langat / Puteri Natasya Firnando and Suzana Ramli - Firnando, Puteri Natasya; Ramli, Suzana Ramli (2023)
Flooding is a sort of natural disaster that can occur anywhere in the world. It is also happening more often now because of global warming and climate change. The Department of Irrigation and Drainage (DID) has designated certain sites along the Lui River in Hulu Langat as flood-prone. Therefore, this study presents a hydrological simulation of the Lui River utilising the flood management software on the Hydrologic Modelling System, HEC-HMS 4.8, which has been widely used in several studies of water management. The program replicates a river basin system's rainfall-runoff response to a precipitation input by modelling the whole river basin as an integrated system of hydrologic and hydraulic components, displaying the trends in the river's flow for 50 ARI and 100 ARI. The hydrograph of the Lui River may be determined by examining the rainfall-runoff relationship and comparing it to the peak discharge of observed data and the hydrograph for an unmeasured watershed from Hydrological Procedure No. 11. The hydrograph result must undergo model calibration to establish parameters that are validated for the model final value of peak discharge and the shape of the hydrograph. The finding shows that the optimal design hydrograph for the design stage is the model's hydrograph with the greatest peak as in HEC-HMS. Hence, the design storm with the largest output will serve as a guideline for any design matter, be valuable for future river flow research, and function as a future precaution.